Tinjauan Sosiologi Hukum Tentang Aksi Vandalisme Terhadap Fasilitas Umum Di Kota Bandar Lampung - Zainudin Hasan; Anugrah Aditya Ramadhan; Hattal Musyafa; Apta Zaki Albiruni (Jurnal Konstruksi Hukum, 2023)
Vandalism is the destruction of someone else's property or public property. One of the articles of the Criminal Code used to identify vandalism is Article 406 of the Criminal Code which does not specifically mention writing and only uses the terms destruction and destruction. Thus, the use of the words destructive and destructive in the use of the words destructive and destructive in Article 406 of the Penal Code remains incomprehensible, since the provision does not specifically regulate writing. The study was conducted by interviewing perpetrators of crime, police and the public, and juvenile crime was seen as a concern, particularly related to freedom of expression, which was not well monitored. This is a problem that must be faced together and is the shared responsibility of both education groups, including families, schools and law enforcement officials such as the police, prosecutors and courts. The government as a determinant of security starts from the stage of security, security, and security competition, as well as community order.